The Effect Of Organizational Balance On Job Satisfaction (Field Study In Private Universities Operating In Lattakia) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The aim of the study is to show the effect of organizational balance on job satisfaction through (promotion, work environment, work content) in private universities in Lattakia. Distributed to (141) respondents in a comprehensive inventory method, (138) were recovered from them, while (6) a questionnaire that was not valid for analysis was rejected, due to the lack of seriousness in filling out information, it was (132) a questionnaire that was valid for analysis, and the research community consisted of a cadre of workers in university branches Private Al-Sham Private University, Lattakia Branch, the Arab Academy for Science, Technology and Maritime Transport, Lattakia Branch. The researcher concluded the following: The salary satisfies the basic needs of the workers, the amount of the salary motivates the worker to perform his work at the best level, and the rewards make the worker work seriously.The researcher recommends the following: that universities should pay attention to the salary so that it satisfies the basic needs of workers, by paying attention to incentives, rewards and promotions, and ensuring that the worker receives the salary that guarantees him a better life. Between employees, such as granting employees equal material and moral incentives quarterly, semi-annually or annually.